2010
DOI: 10.1088/0004-637x/716/1/1
|View full text |Cite
|
Sign up to set email alerts
|

The Milky Way Tomography With Sdss. Iii. Stellar Kinematics

Abstract: We study Milky Way kinematics using a sample of 18.8 million main-sequence stars with r < 20 and proper-motion measurements derived from SDSS and POSS astrometry, including ∼170,000 stars with radial-velocity measurements from the SDSS spectroscopic survey. Distances to stars are determined using a photometric parallax relation, covering a distance range from ∼100 pc to 10 kpc over a quarter of the sky at high Galactic latitudes (|b| > 20 • ). We find that in the region defined by 1 kpc < Z < 5 kpc and 3 kpc <… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
182
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(202 citation statements)
references
References 78 publications
18
182
1
1
Order By: Relevance
“…Local studies, limited to heliocentric distances D10 kpc, have measured the full 3D kinematics of halo stars. This has revealed a strongly radially biased velocity anisotropy with 1 0.5 0.7 tan 2 rad 2 -b s s = -» (e.g., Smith et al 2009;Bond et al 2010), in seemingly good agreement with the predictions of simulations (e.g., Bullock & Johnston 2005;Cooper et al 2010).…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Local studies, limited to heliocentric distances D10 kpc, have measured the full 3D kinematics of halo stars. This has revealed a strongly radially biased velocity anisotropy with 1 0.5 0.7 tan 2 rad 2 -b s s = -» (e.g., Smith et al 2009;Bond et al 2010), in seemingly good agreement with the predictions of simulations (e.g., Bullock & Johnston 2005;Cooper et al 2010).…”
Section: Introductionsupporting
confidence: 78%
“…Our measurement of β, from the 3D kinematics of N=13 stars in the radial range 18r/kpc32, is shown in pink. Solar neighborhood measurements, using full 3D velocity information, find a radially biased β, shown in red Bond et al 2010). The remaining error bars show estimates of β for distant (D10 kpc) halo stars using LOS velocity distributions (Sirko et al 2004;Deason et al 2012;Kafle et al 2012;King et al 2015).…”
Section: A Galactic Shellmentioning
confidence: 96%
“…They measured the PMs of 13 stars at 24 ± 6 kpc toward the Andromeda-Triangulum halo overdensity, which imply a halo velocity ellipsoid that is roughly isotropic. This is more tangential than the velocity ellipsoid of halo stars near the Sun, which is measured from ground-based PMs to be highly radially anisotropic (e.g., Bond et al 2010). These results are consistent with the hypothesis that the Andromeda-Triangulum overdensity may be a shell in the halo, possibly resulting from an ancient accretion event.…”
Section: Metal-poor Halosupporting
confidence: 81%
“…For halo tracers, profile of the radial velocity dispersion σr can be easily estimated from the line-of-sight velocity dispersion σ los (Battaglia et al 2005;Dehnen et al 2006), while their number density is found to follow a double power law with a break radius r b around 20 kpc (Bell et al 2008;Watkins et al 2009;Deason et al 2011;Sesar et al 2011). However, the anisotropy parameter β has only been accurately measured in the solar neighborhood, with a radially biased value between 0.5 -0.7 (Kepley et al 2007;Smith et al 2009;Bond et al 2010;Brown et al 2010). Due to the lack of accurate proper motion measurements of distant halo tracers, the anisotropy parameter β is still poorly constrained beyond the solar neighborhood, particularly for the outer halo (> 25 kpc).…”
mentioning
confidence: 99%